Permainan Flashcard Fun Time untuk Mengenalkan Kosakata Bahasa Inggris pada Anak Usia Dini - Laela, Nur; Imani Khan, Rosa; Kurnia Wati, Epritha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study develops the Flashcard Fun Time game to introduce English vocabulary to early childhood. The approach uses Research and Development (R&D) with three stages: information gathering through literature review, design planning, and preliminary product development with feasibility evaluation. Validation was conducted by three material and three game experts using a 1–5 Likert Scale questionnaire, analyzed with Aiken's V index. Results showed all aspects had Aiken's V ≥ 0.5 with averages of 0.84 (material) and 0.83 (game experts), indicating Flashcard Fun Time is valid and feasible. The product combines hand-shaped flashcards, interactive PowerPoint, and digital spinner for multimodal (visual, auditory, kinesthetic) enjoyable learning. Conclusion: Flashcard Fun Time is an effective innovative media for introducing English vocabulary to early childhood.